(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The purpose of this research is to find out the relationship and significance impact of utilizing Mobile Assistance Language Learning (MALL) through Hello English Application as learning media on student’s vocabulary mastery. The quantitative method was used by researcher because the data will be processed in numerical form and statistical analysis. In this research is conducted without a control group, so the data analysis used pre experimental research design one group pretest- posttest. The sample of the research was consisted of 25 students at seventh grade of MTS Salafiyah Pajarakan in academic Year 2022/2023. The data was collected by using test which consisted of pre-test and post-test. The Wilcoxon signed-rank test resulted z-score of -4.298 with a p-value (Asymp.Sig. (2-tailed). The significance value is 0.000 less than 0.05, so the hypothesis decision is to accept Ha and reject Ho. It means that there is a significant difference between the pre-test and the post-test. It can be concluded that using Hello English application as an English learning media has a significant impact on students’ skill vocabulary acquisition. It is proved by a significant difference between the mean pretest and posttest score.The result of this research indicates that there is a significant impact in the use of Hello English App as a learning media for students’ vocabulary mastery skill.